Author Correction: Matrix-producing neutrophils populate and shield the skin (Nature, (2025), 10.1038/s41586-025-08741-5) - Vicanolo, Tommaso; Özcan, Alaz; Li, Jackson Liang Yao; Huerta-López, Carla; Ballesteros, Iván; Rubio-Ponce, Andrea; Dumitru, Andra C.; Nicolás-Ávila, Jose Ángel; Molina-Moreno, Miguel; Reyes-Gutierrez, Pablo; Johnston, Andrew D.; Martone, Catherine; et al. (Nature, 2025)
Correction to: Naturehttps://doi.org/10.1038/s41586-025-08741-5 Published online 19 March 2025 In the version of the article initially published, in the “Mice” paragraph of the Methods, the text “The mouse sequence for the CNA35-mCherry cassette was obtained from Dr. Rinkevich at Helmholtz Zentrum Munchen” was missing and has now been added. Similarly, the text “Dr. Mück-Häusl and Dr. Rinkevich at Helmholtz Zentrum München for help designing the CNA35-reporter mice” was missing from the Acknowledgements section and has now been added. These corrections have been made to the HTML and PDF versions of the article.
CRIS-Team Scopus Importer:2025-05-16

Fetal liver macrophages contribute to the hematopoietic stem cell niche by controlling granulopoiesis - Kayvanjoo, Amir Hossein; Splichalova, Iva; Bejarano, David Alejandro; Huang, Hao; Mauel, Katharina; Makdissi, Nikola; Heider, David; Tew, Hui Ming; Balzer, Nora Reka; Greto, Eric; Osei-Sarpong, Collins; Baßler, Kevin; et al. (eLife, 2024)
During embryogenesis, the fetal liver becomes the main hematopoietic organ, where stem and progenitor cells as well as immature and mature immune cells form an intricate cellular network. Hematopoietic stem cells (HSCs) reside in a specialized niche, which is essential for their proliferation and differentiation. However, the cellular and molecular determinants contributing to this fetal HSC niche remain largely unknown. Macrophages are the first differentiated hematopoietic cells found in the developing liver, where they are important for fetal erythropoiesis by promoting erythrocyte maturation and phagocytosing expelled nuclei. Yet, whether macrophages play a role in fetal hematopoiesis beyond serving as a niche for maturing erythroblasts remains elusive. Here, we investigate the heterogeneity of macrophage populations in the murine fetal liver to define their specific roles during hematopoiesis. Using a single-cell omics approach combined with spatial proteomics and genetic fate-mapping models, we found that fetal liver macrophages cluster into distinct yolk sac-derived subpopulations and that long-term HSCs are interacting preferentially with one of the macrophage subpopulations. Fetal livers lacking macrophages show a delay in erythropoiesis and have an increased number of granulocytes, which can be attributed to transcriptional reprogramming and altered differentiation potential of long-term HSCs. Together, our data provide a detailed map of fetal liver macrophage subpopulations and implicate macrophages as part of the fetal HSC niche.
CRIS-Team Scopus Importer:2024-11-15
Keywords: developmental biology; fetal liver; granulopoiesis; hematopoiesis; hematopoietic stem cells; immunology; inflammation; macrophages; mouse